Human Tissue Kallikrein: A New Bullet for the Treatment of Ischemia - Emanueli, C.; Madeddu, P. (Current Pharmaceutical Design, 2003)
Recently, therapeutic angiogenesis has been proposed as an alternative for the treatment of ischemic diseases unresponsive to conventional therapy. This strategy is based on the concept that a supply-side approach with growth factors would overcome the endogenous deficit and result in more robust collateralization. We have developed a strategy based on local delivery of human tissue kallikrein gene for potentiation of microcirculation and rescue of peripheral ischemia. Following successful application in otherwise healthy animals, the approach resulted to be of therapeutic value in rats with endothelial dysfunction caused by arterial hypertension. In addition, human tissue kallikrein prevents or rescues microvascular rarefaction caused by diabetes mellitus. In this model, human tissue kallikrein was able to stimulate vascular growth and contrast apoptosis. The strategy displays interesting pharmacological features because is devoid of obvious side effects and is effective even at low infecting doses. In addition, the neovascularization promoted by human tissue kallikrein is well organized and durable. It is reasonable to anticipate that the new approach will have a great impact in the treatment of cardiovascular ischemic complications.
Keywords: diabetes